Effectiveness of the revision to FMVSS 301: FARS and NASS-CDS analysis of fatalities and severe injuries in rear impacts. (April 2016) - Viano, David C.; Parenteau, Chantal S.
Abstract: Purpose: This study investigated the change in the fatality and severe injury risks in rear impacts with vehicle model years (MY) grouped prior to, during the phase-in and after the revision to FMVSS 301. Methods: FARS and NASS-CDS data were used to determine the injury risks of non-ejected occupants in light vehicles involving non-rollover, rear impacts. The data were analyzed by MY groups: 1996–2001, 2002–2007 and 2008+ to represent the years prior to, during the phase-in and post-revision phase-in of FMVSS 301. The 1996–2013 FARS data were analyzed for rear crashes defined by the initial crash direction (IMPACT1) and direction with most damage (IMPACT2) to the rear. Fatality risk was determined by the number of fatally injured occupants per all occupants with known injury status. The 1994–2013 NASS-CDS was analyzed for rear crashes defined by the damage area variable. The risk of severe injury (MAIS 4+F) was determined as the number of occupants with MAIS 4+F injury per all occupants with known injury status. The distribution of rear crashes was determined by impact location and crash severity. NASS-CDS electronic cases with 2008+ MY vehicles were analyzed to evaluate the vehicle and occupant performance. Results: The fatality risk was 20.6% in the 1996–2001, 17.3% in the 2002–2007 and 15.0% in the 2008+ MY vehicles using FARS with the initial crash direction variable (IMPACT1) to the rear. There was a 27.1% reduction in risk with post-FMVSS 301 vehicles 2008+ MY. The risk was 19.0%, 15.4% and 12.8% with the most damage variable (IMPACT2) to the rear. There was 32.8% reduction in risk with 2008+ MY vehicles. The NASS-CDS analysis showed that the risk of severe injury (MAIS 4+F) was 0.27 ± 0.05% for 1996–2001, 0.30 ± 0.13% for 2002–2007 and 0.08 ± 0.04% for 2008+ MY year vehicles. There was a 70.2% reduction in the risk for severe injury with 2008+ MY vehicles. The NASS-CDS case review of MAIS 4+F injury in rear impacts of 2008+ MY vehicles that comply with the revised FMVSS 301 indicated that the crashes were very severe and generally involved significant 2nd row intrusion. Conclusions: The revision to FMVSS 301 has effectively reduced the risks for fatal and severe injury in vehicles compliant with the revision (2008+ MY). The reduction was 27.1–32.8% in fatality risk using FARS data and 70.2% in severe injury risk using the NASS-CDS when compared to vehicles prior to the phase-in of the revised FMVSS 301 (1996–2001 MY vehicles). It is not possible to parse the effects of other design changes in seats and restraint systems that also increased safety over the study years.